2016
DOI: 10.1152/physiol.00033.2015
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Growth Restriction: Hungry for an Answer

Abstract: Intrauterine growth restriction (IUGR) has been defined in several ways, but in general describes a condition in which the fetus exhibits poor growth in utero. This complication of pregnancy poses a significant public health burden as well as increased morbidity and mortality for the offspring. In human IUGR, alteration in fetal glucose and insulin homeostasis occurs in an effort to conserve energy and survive at the expense of fetal growth in an environment of inadequate nutrient provision. Several animal mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
65
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 134 publications
0
65
0
2
Order By: Relevance
“…Current reviews suggest maternal or neonatal nutrient supplementation has little impact in mitigating IUGR in humans (Brown et al 2011; Devaskar and Chu 2016; Hay 2008). Furthermore, most nutritional interventions are associated with increased adiposity and not increased linear growth.…”
Section: Future Directionsmentioning
confidence: 99%
“…Current reviews suggest maternal or neonatal nutrient supplementation has little impact in mitigating IUGR in humans (Brown et al 2011; Devaskar and Chu 2016; Hay 2008). Furthermore, most nutritional interventions are associated with increased adiposity and not increased linear growth.…”
Section: Future Directionsmentioning
confidence: 99%
“…Intrauterine growth restriction (IUGR) is characterized by insufficient growth of the fetus during pregnancy, resulting from an adverse maternal environment, such as poor nutrition or reduced oxygen supply at the fetomaternal interface [Devaskar and Chu, ]. IUGR is associated with a high incidence of perinatal morbidity and mortality, short‐term and long‐term metabolic and cardiovascular alterations and neurological disorders [Zohdi et al, ; Cohen et al, ].…”
mentioning
confidence: 99%
“…It is characterized as a rate of fetal growth of less than normal for the gestational age-appropriate growth potential [1, 2]. The diagnosis of IUGR is usually assigned to infants with a birth weight < 10th percentile for gestational age and called small for gestational age (SGA) [3].…”
Section: Introductionmentioning
confidence: 99%
“…A number of autopsy studies have reported a significant reduction in nephron numbers as a result of IUGR [1, 10]. The linear relationship was reported between the number of glomeruli (and therefore nephrons) and birth weight in full-term neonates; neonates < 10th percentile of birth weight had 30% fewer glomeruli than those with birth weights > 10th percentile [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation